Kelompok Nelayan dan Wanita Nelayan di Selakau dan Pemangkat dalam Pengolahan Udang Rebon Menjadi Bubuk Terasi Kering - Nurliza, Nurliza; Dolorosa, Eva; Hartanti, Lucky (Universitas Tanjungpura, 2018)
In Selakau and Pemangkat, Sambas district, has the largest shrimp carts, particularly as Togok season, February to May. Everyday, each group of fishermen caught the shrimp for 50 kg to 1 tons. However, they faced some obstacles. In the rainy season, the catch was quickly decompose due to the absence of cool storage so that the shrimp are processed into solid pasta and pack it in a piece of newspaper, leaves or ordinary plastic. As the result, the durability and the quality of products are limited and had poor quality. Thus, the stakeholders, especially the local government be worried about the miss an opportunity to get added value in shrimp processed into a solid paste which could be taken by stakeholders of other regions through the innovation of a package which made the products more attractive with specific brands. This IbM tried to improve the self-sufficient and capable of group of fisherman and their women in solid paste of shrimp processing into powder which had the longer durability to get more added value. IbM was designed with training and practice. The results shown that solid paste of shrimp was processed into powder; polypropylene plastic packaging was used to get safety, durable, and hygienic products; the product had a label with an attractive design; certificate of training; PIRT license; some tool aids, i.e. The cool storage, impulse sealer power pack, vacuum sealer, digital scales, drying oven, hand plastic sealer, sieving, the lighters, seals, labels, cutting board, apron, etc.